Storage stability of an egg yolk cream formulation: texture and microbiological assessment - Fundo, Joana F. (2010)
BACKGROUND: Egg yolk cream is confectioned with egg yolk, sugar and water. Pasteurized liquid eggs may be used in order to increase product safety, although these samples may differ from the classic ones produced with raw eggs. The objective was to evaluate and compare the stability (physicochemical characteristics, such as texture assessment, pH and water activity, and microbiological assessment) of a classic formulation and an alternative one produced with pasteurized eggs, during storage at 6, 26, 30 and 37◦C. RESULTS: From a microbiological point of view (mesophile and psychrotrophic activity), no differences were observed in either formulations.At 6 and 26 ◦C, rheological behaviour of both formulations remained approximately constant. At 30 and 37 ◦C, differences were only detected after 20 days of storage. Texture was better retained in samples prepared with pasteurized eggs, while the classic samples showed an increase in complex viscosity. CONCLUSION: Cream storage did not require refrigeration. In terms of texture and microbial load, results obtained at 6 and 26 ◦C were identical. The formulations only differed in texture when stored at 30 and 37 ◦C and for long periods. These conclusions may allow reduction of costs related to refrigerated distribution/storage of either classic or alternative formulations.